Macroscopic Fungi in Grassland and Rubber Plantation Habitat Types in Special Purpose Forest Areas of Universitas Lambung Mangkurat, Indonesia - Lefi, Elsa Lenia; Soendjoto, Mochamad Arief; Fitriani, Adistina; Riefani, Maulana Khalid (Biota, 2024)
In addition to secondary natural forests, other habitat types that also exist in the Special Purpose Forest Area of Universitas ​​Lambung Mangkurat (KHDTK ULM) are grasslands and rubber plantations. While previous studies have documented macroscopic fungal species in secondary natural forests, there has been no documentation on fungi in the last two habitat types. This study aimed to analyze macroscopic fungal species present in these two habitat types and the substrates they inhabit. Fungal species and their substrates were recorded on a 250 m x 8 m track between May and September 2024. Each track was placed at threelocations representing grasslands and three locations representing rubber plantations. In total, ten fungal species were found in grasslands and 7 species in rubber plantations. The similarity index of the fungal communities in the two habitats was categorized as very low (23.53%). Additionally, more fungal species were found on substrates such as dead trunks (rotten wood) compared to those found in the soil